Dnmt3a knockout in excitatory neurons impairs postnatal synapse maturation and increases the repressive histone modification H3K27me3 - Li, Junhao; Pinto-Duarte, Antonio; Zander, Mark; Cuoco, Michael S; Lai, Chi-Yu; Osteen, Julia; Fang, Linjing; Luo, Chongyuan; Lucero, Jacinta D; Gomez-Castanon, Rosa; Nery, Joseph R; Silva-Garcia, Isai; et al. (eLife, 2022)
Two epigenetic pathways of transcriptional repression, DNA methylation and polycomb repressive complex 2 (PRC2), are known to regulate neuronal development and function. However, their respective contributions to brain maturation are unknown. We found that conditional loss of the de novo DNA methyltransferase Dnmt3a in mouse excitatory neurons altered expression of synapse-related genes, stunted synapse maturation, and impaired working memory and social interest. At the genomic level, loss of Dnmt3a abolished postnatal accumulation of CG and non-CG DNA methylation, leaving adult neurons with an unmethylated, fetal-like epigenomic pattern at ~222,000 genomic regions. The PRC2-associated histone modification, H3K27me3, increased at many of these sites. Our data support a dynamic interaction between two fundamental modes of epigenetic repression during postnatal maturation of excitatory neurons, which together confer robustness on neuronal regulation.
Keywords: epigenetics; synapse; brain development; DNA methylation; Dnmt3a; H3K27me3